Concentration-dependent SILAR synthesized Di-bismuth copper oxide nano-materials electrode in asymmetric supercapacitor - Bobade, R. G.; Dabke, N. B.; Shaikh, Shoyebmohamad F.; Al-Enizi, Abdullah M.; Pandit, Bidhan; Lokhande, B. J.; Ambare, R. C. (Journal of Materials Science-Materials in Electronics, 2024)
In this study, we present a novel approach to prepare bismuth oxide deposited on copper substrate (Bi2CuO4) electrodes using a binder-free successive ionic layer adsorption and reaction (SILAR) technique, demonstrating their potential for energy storage applications. The resulting Bi2CuO4 electrode exhibits a tetragonal crystal structure with a polycrystalline nature, as confirmed by X-ray diffraction (XRD). Field emission scanning electron microscopy (FE-SEM) reveals a distinctive sphere-like structure with hydrophilic characteristics, as determined from contact angle measurements. X-ray photoelectron spectroscopy (XPS) further validates the composition of the sample. The electrochemical performance of Bi2CuO4 is remarkable, with a specific capacitance (SC) of 1795.9 F/g at 16 mA/cm(2). When used as an anode in an asymmetric solid-state device (ASSD) alongside activated carbon (AC) as the cathode, the Bi2CuO4 electrode attains a maximum energy density (SE) of 169.5 Wh/kg at 16 mA/cm(2) and a peak power density (SP) of 15.9 kW/kg at 24 mA/cm(2). In a 1 M KOH-polyvinyl alcohol (PVA) polymer solution, the Bi2CuO4//AC pencil-type cell achieves a superior SC of 94.5 F/g at 5 mV/s, retaining approximately 92% of its initial performance even after 5000 charge-discharge cycles. The resulting SE and SP are 43.1 Wh/kg and 5.2 kW/kg at 10 mA/cm(2), respectively. This research presents an efficient and straightforward synthesis method for producing high-performance pencil-type supercapacitors at a laboratory scale. Furthermore, we demonstrate the potential of a homemade pencil-type supercapacitor device (Bi2CuO4//AC) to power a light-emitting diode (LED), highlighting its practical utility in various energy storage applications.

Electrochemical property of nanosphere-like MgO electrode synthesized via SILAR in asymmetric supercapacitor - Gaikwad, D. S.; Bobade, R. G.; Suryawanshi, V. B.; Nakate, U. T.; Shaikh, S. F.; Al-Enizi, Abdullah M.; Dabke, N. B.; Lokhande, B. J.; Ambare, Revanappa C. (Journal of Materials Science-Materials in Electronics, 2024)
In this research article, we synthesized nanospheres of MgO thin-film substrate using the successive ionic layer adsorption and reaction (SILAR) technique on stainless steel substrates. The final optimized sample was used for physical characterization. XRD revealed the cubic structure of the MgO electrode. Additionally, it was utilized for electrochemical supercapacitive characterization, including cyclic voltammetry (CV), chronopotentiometry, and electrochemical impedance spectroscopy (EIS). Results showed that MgO nanospheres exhibited a higher specific capacitance (SC) of 536.06 F/g. The maximum values of specific energy and specific power were 30.79 Wh/kg and 1420 W/kg, respectively, at 2 mA/cm2 in 1-M KOH. The EIS plot confirmed an internal resistance (Ri) of 0.86 omega, indicating good power performance and outstanding rate capability of MgO nanospheres. This material demonstrated excellent cycling capability, retaining 91.38% capacitance after 5000 CV cycles. The MgO//AC device displayed an SC of 210.21 F/g at 5 mV/s in a PVA-KOH solid-state electrolyte. With an energy density of 23.90 Wh/kg and a power density of 1.84 kW/kg, the asymmetric supercapacitor performance showed that the MgO-based electrode is suitable for use in actual device manufacturing. After 5000 CV cycles, the supercapacitor device exhibited exceptional capacitance retention of 92.93%. Thus, this research successfully demonstrated the usefulness of the simple and affordable SILAR method for synthesizing pure MgO nanostructures for application in supercapacitors.

Influence of deposition potential on electrodeposited bismuth-copper oxide electrodes for asymmetric supercapacitor - Bobade, Rushikesh G.; Dabke, Niteen B.; Shaikh, Shoyebmohamad F.; Al-Enizi, Abdullah M.; Pandit, Bidhan; Lokhande, Balkrishna J.; Ambare, Revanappa C. (BATTERIES & SUPERCAPS, 2024)
Keywords: Bi2CuO4; Deposition Potential; Electrodeposition; supercapacitor; thin film